(untitled) (Physical Education, Health and Social Sciences, 2025)
Current research work aims at eco-friendly pathway of synthesizing functional iron oxide thin films on fluorine doped tin oxide (FTO) a transparent glass substrate, through pyrolysis of 4-nitrophenylferrocene, an organometallic precursor. The sample slide S-1 obtained by the fabrication of iron oxide thin film on FTO having (dimensions 40 x 40 x 2mm) using exact 0.1 g of 4-nitrophenylferrocene in small crucible followed by heating in an electric furnace above 450 OC. Finally annealing at 750 OC for 10 minutes, a uniform reddish brown colored thin film of iron oxide was successfully fabricated with clear and flat surface. The Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) employed to monitor surface morphological aspects and elemental analysis and confirmed the presence of Fe and O atoms. The sample slide S-1 was functional and showed potential photocatalytic performance when used to degrade toxic water waste organic dye methylene blue under the sunlight. The sample slide S-1, degraded 49% of methylene blue in 30 minutes, the ability was measured using UV/Visible spectroscopy.